A proposal for the improvement of financial academic processes: process modelling and analysis in NOVA IMS - Oliveira, Filipe Aparício (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management